2022
DOI: 10.4018/ijirr.295974
|View full text |Cite
|
Sign up to set email alerts
|

A Text Mining Framework for Analyzing Change Impact and Maintenance Effort of Software Bug Reports

Abstract: Software practitioners often strive to achieve a “bug-free” software, though, it is a myth. Software Bug Categorization (SBC) models, which assigns levels (viz. “low”, “moderate” or “high”) to a software bug aid effective bug management. They assist in allocation of proper maintenance resources for bug elimination to improve software quality. This study proposes the development of SBC models that allocate levels on the basis of three software bug aspects i.e., maintenance effort required to correct a bug, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…After evaluation, it was found that the performance of the combined SBC model showed higher accuracy than the ME or CI SBC models. They also found that the accuracy of the "high" category was superior to that of the other categories [7]. R Malhotra et al have worked to find out if resampling methods applied to software defect data improve performance.…”
Section: Related Workmentioning
confidence: 99%
“…After evaluation, it was found that the performance of the combined SBC model showed higher accuracy than the ME or CI SBC models. They also found that the accuracy of the "high" category was superior to that of the other categories [7]. R Malhotra et al have worked to find out if resampling methods applied to software defect data improve performance.…”
Section: Related Workmentioning
confidence: 99%